Sifat Mekanik dan Biodegradabilitas Biokomposit Berbasis Polyvinyl Alcohol dan Pati Kentang dengan Pennisi Serbuk Kulit Lemon - Revvan Rifada Pradiza; Firnanda Risky Ramadhana; Muhammad Yusuf; Mochamad Asrofi; Yayang Permadi; Dwi Heru Siswantoro; Deny Tomy Andrianto; Alfi Hasan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to examine the mechanical properties, surface morphology, and biodegradability of polyvinyl alcohol-potato starch biocomposites with lemon peel powder as a filler. The biocomposites were produced by solution casting with 1%, 2%, and 3% fillers of lemon peel powder. Mechanical properties were tested to determine tensile strength in accordance with ASTM D882. The addition of lemon peel powder increased tensile strength as the percentage content increased. The highest tensile strength was 4.82 MPa in polyvinyl alcohol-potato starch biocomposites containing 3% lemon peel powder. This indicates that lemon peel powder effectively improves bonding with the matrix and produces stronger interfacial bonds. However, the flexibility of the biocomposites decreased with increasing lemon peel powder content, as indicated by a decrease in elongation. Furthermore, the biodegradation of the biocomposites showed that the biocomposite with the highest lemon peel powder content (3%) exhibited the fastest degradation rate, reaching 65.22% after 15 days of testing. These results indicate that the presence of lemon peel powder improves the mechanical properties of the biocomposite without reducing its biodegradability. These findings indicate that biocomposites made from polyvinyl alcohol and potato starch with lemon peel powder are a promising sustainable plastic alternative, combining strength, flexibility, and degradability.